Rice bran oil as emerging green fuels: exploration on combustion behaviours of single cylinder diesel engine (light-duty engine) - Mohamed, Norhafana; Ihsan, Che Ku; Mat Noor, Muhamad; Hairuddin, Abdul Aziz; Indra Mahlia, Teuku Meurah; Kadirgama, Kumaran; Ramasamy, Devarajan; Samykano, Mahendran; Ghazali, Mohd Fairusham; Rahman, Md Mustafizur (Semarak Ilmu Publishing, 2024)
In the current work, an experiment was conducted to examine the combustion properties of a single cylinder compression ignition direct ignition engine fuelled with rice bran oil at different engine loads. The investigation focused on the analysis of cylinder pressure and exhaust gas temperature as key factors in combustion. The fuel blends utilized in this study consist of various proportions of diesel and rice bran oil, including 100% pure diesel (RBO00), a blend of 25% rice bran oil and 75% pure diesel (RBO25), a blend of 50% rice bran oil and 50% pure diesel (RBO50), a blend of 75% rice bran oil and 25% pure diesel (RBO75), and 100% rice bran oil (RBO100). Comparisons are made between the results of an experiment using rice bran oil (RBO25, RBO50, RBO75, and RBO100) and a diesel engine (RBO00). RBO00 exhibits a greater heat output per unit mass compared to RBO25, RBO50, RBO75, and RBO100 blends because of the highest value of calorific value (CV) among others blends. Consequently, RBO00 demonstrated a higher measurement of exhaust gas temperature (EGT). One further contributing factor was the increased exhaust gas temperature (EGT), which led to an extended ignition delay, resulting in a lengthier fuel combustion process and the egress of combustion gas from the combustion chamber at higher temperatures. RBO100 achieved the highest cylinder pressure in both 50 % and 100 % engine load settings. The RBO100 blends fuel successfully achieved the optimal cylinder pressure in both 50 % and 100 % engine load conditions. The cylinder pressure for RBO00 (pure diesel) was the lowest at both half and full loads. The observed decrease in peak pressure can be attributed to the decreased cetane number (CN) and oxygen concentration found in RBO00 in comparison to the mixed fuels of RBOs. This will affect the completion of combustion such as wear and tear for the cylinder and piston. Under both 50 % and 100 % engine load condition, the cylinder pressure for RBO00 (pure diesel) was the lowest. In summary, rice bran oil showed superior combustion behaviour compared to pure diesel, and the mixture blends RBO75 and RBO100 can be thought of as ideal in terms of exhaust gas temperature and cylinder pressure.